The use and impact of the Rehabilitation of Offenders Act (1974): a final report - McGuinness, Paul (Report, 2013)
1. This research arises from a current Government review of the Rehabilitation of Offenders Act (1974). It considers how recent changes to it may affect offender rehabilitation and employment opportunities, and how employers and ex-offenders perceive and are affected by the law. 2. Criminal convictions are an issue for a considerable portion of the Scottish population. Scottish Government analysts have analysed data from the Scottish Offenders Index to produce actual and estimated numbers of persons within the Scottish population having a criminal conviction. This analysis showed that over 38% of men and 9% of women born in 1973 are known to have at least one criminal conviction. Extrapolating to the population as a whole, at least one-third of the adult male population and nearly one in ten of the adult female population is likely to have a criminal record. 3. Criminal records checks are now a regular experience for many people. Currently over one million applications for basic disclosure of criminal convictions are processed every year by Disclosure Scotland. Recent changes have included the creation of a heightened checking scheme for people working with vulnerable groups. 4. Research and review have increasingly raised questions about the ability of the Act to support the smooth integration of people with historical criminal convictions. Rehabilitation periods set out in law have been criticised as too long in light of research on the declining risks of recidivism over time as well as research on the stigmatising effect of waiting for a criminal record to expire. Amendments to the Act have increased the range of professions and situations that are exempted from the Act. 5. Employment is one of the most strongly correlated predictors of reduced reoffending. Not only does it help establish financial stability, but also roots a range of positive social relationships and bases of identity. However, amendments to the ROA which increasingly exempt professions in health and social welfare sectors may be exacerbating barriers to employment for ex-offenders in a labour market where such professions are expanding relative to industrial and manufacturing jobs. 6. Surveys of employers regularly show a lack of knowledge about the ROA and a bias against recruitment of ex-offenders, although there are important exceptions to this particularly where an employer has had prior experience of interviewing or hiring ex-offenders. Most employers who have taken the time to interview or have employed ex-offenders reported positive experiences and a willingness to further recruit from this group. 7. Ex-offenders report experiences of feeling discouraged, stigmatised and being wrongly questioned about their backgrounds when attempting to gain access to employment and education. These perspectives show how legislative frameworks and employer attitudes which affect recruitment of ex-offenders have an effect not only on the employment rates of people trying to reintegrate into society but also on their long-term psychological and general well-being. 8. This report sets out three possible approaches to reform, graduating in the degree to which they would alter existing practices and presumptions. The most minimal modification of the Act’s rehabilitation periods would reduce the passive waiting time. Providing a certificate of rehabilitation would create a more active mode of acknowledging restoration of a person’s status as a welcomed member of society. Judicial imposition of occupational disqualification shift focus onto the specific exclusion from certain jobs where a case by case analysis determines this is appropriate.